Understanding Neoproterozoic geodynamics through Hafnium isotope arrays - Martin, Erin Lee (Curtin University, 2020)
The Neoproterozoic supercontinent Rodinia assembled by the collision of a global-scale subduction girdle at the end of the Mesoproterozoic. A new subduction girdle is not established until the assembly of Gondwana some 500 Ma later, at the end of the Neoproterozoic. Thus, the global Hf isotope record suggests that the Neoproterozoic was dominated by the degree-1 condition, which facilitated Gondwana amalgamation, but it is not clear that degree-2 mantle convection facilitated the breakup of Rodinia.